The Impact of Interactive Learning Media to Increase Interest in Learning Physical Education - Indah Verawati; Rahma Dewi; Muhammad Reza Destya (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Interest in learning physical education is often less than optimal due to the use of less innovative learning media. Interactive learning media offers the potential to increase learning interest, but its effectiveness needs to be further analyzed. This study aims to analyze the impact of using interactive learning media on increasing interest in learning physical education using inferential analysis. This type of research is an experiment with a one-group pretest-posttest design. The research subjects consisted of 40 students who took the small ball game course. The data collection methods used in this study were tests and questionnaires of interest in learning before and after treatment (interactive learning media) and using instruments in the form of questionnaire sheets. After the data is collected then analyzed using parametric statistical tests. The results showed that interactive learning media significantly increased interest in learning physical education, with differences in pretest and posttest scores supporting the research hypothesis. The conclusion shows that interactive learning media is effective in increasing interest in learning, providing implications for educators to utilize similar media to improve the quality of learning.